Optimisation of 4D (project timeline) and 5D (budget analysis) in building information modelling (BIM) for house refurbishment and renovation - Nurdini Atiqah Talib (2022)
The potential of 4D and 5D Building Information Modelling (BIM) have been proven to facilitate project timeline and budget analysis in construction industry, however the implementation of 4D and 5D BIM in house renovation and refurbishment is still underdeveloped especially in Malaysia. Therefore, this study was conducted purposedly to identify the advantages of 4D and 5D BIM, to analyse the level of awareness of 4D and 5D BIM implementation and to pave a proper strategy for house refurbishment and renovation using BIM in Malaysia. The method uses to achieve the objectives was questioners survey that was analyse using SPSS and modelling using Autodesk Revit for 3D model and Navisworks Manage for 4D and 5D BIM. The selected model is based on the two and a half storey terrace houses at Taman Bukit Sepangar Kota Kinabalu Sabah. This study manages to collect 45 responded from construction player. The results revealed that the significant advantages of 4D BIM are early simulation that will detect any clashes which usually lead to construction delay with mean rank of 4.36, 4D BIM could provide a clear walk through before the construction begin rated second with 4.22 mean rank and 4D BIM could serve as centralized data rated third with 4.20 mean rank. 5D BIM on the other hand will significantly contribute to faster and accurate quantity take off with scored of 4.40 mean rank, forecast early cost estimation and can improve collaboration between project stockholders on early stage of construction rated second and third with mean rank of 4.29 and 4.20 respectively. However, it is found that the level of BIM implementation in Malaysia currently is still low due to low BIM adoption and unreadiness of organization to adopt BIM. Thus, to carter this problem, it is suggested to set a standard of curriculum at higher institution to train and introduce what is BIM, provide subsidy for BIM software and provide training for construction players will significantly enhance BIM implementation.